1949
DOI: 10.1104/pp.24.4.706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on the Growth and Composition of the Stubble and Roots of Perennial Ryegrass

Abstract: In a previous paper (12) it was reported that, when perennial ryegrass (Olium perennjj .) was partly defoliated, the remaining plant parts underwent a progressive loss in soluble carbohydrates, namely sugars and fructosan, for a period of several weeks. This loss from the stubble and roots accompanied a rapid formation of new tissue above ground. When new top growth had produced sufficient photosynthetic area to manufacture its own organic matter, storage of soluble carbohydrates took place. When the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1957
1957
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…Sullivan and Sprague (1949) observed that as temperature increased from 50° F to 90° F, reduction in root weight following defoliation became greater. Sullivan and Sprague (1949) observed that as temperature increased from 50° F to 90° F, reduction in root weight following defoliation became greater.…”
Section: Interaction Of Clipping With Environmental Factorsmentioning
confidence: 97%
“…Sullivan and Sprague (1949) observed that as temperature increased from 50° F to 90° F, reduction in root weight following defoliation became greater. Sullivan and Sprague (1949) observed that as temperature increased from 50° F to 90° F, reduction in root weight following defoliation became greater.…”
Section: Interaction Of Clipping With Environmental Factorsmentioning
confidence: 97%
“…In cool‐season grasses, the major storage carbohydrate, fructan, is stored in stem bases (Smith, 1967). Fructan concentrations increase in stem bases of cool‐ season grasses, particularly when temperatures decrease in autumn and following reproductive tiller production (Sullivan and Sprague, 1949; Brown and Blaser, 1965; Auda et al, 1966; Smith, 1968; Pollock and Jones, 1979). Fructan that accumulates in autumn is hydrolyzed during spring for production of reproductive tillers and after defoliation for regrowth (Sullivan and Sprague, 1949; Smith, 1967; Labhart et al, 1983; Gonzalez et al, 1989).…”
Section: Carbohydrate Storagementioning
confidence: 99%
“…Fructan concentrations increase in stem bases of cool‐ season grasses, particularly when temperatures decrease in autumn and following reproductive tiller production (Sullivan and Sprague, 1949; Brown and Blaser, 1965; Auda et al, 1966; Smith, 1968; Pollock and Jones, 1979). Fructan that accumulates in autumn is hydrolyzed during spring for production of reproductive tillers and after defoliation for regrowth (Sullivan and Sprague, 1949; Smith, 1967; Labhart et al, 1983; Gonzalez et al, 1989). In response to drought, concentrations of fructan and other water soluble carbohydrates (WSC) decrease in both perennial ryegrass and tall fescue basal tissue (Norris and Thomas, 1982; Suzuki and Chatterton, 1993; Spollen and Nelson, 1994; Volaire and Gandoin, 1996).…”
Section: Carbohydrate Storagementioning
confidence: 99%
“…The percentage of N was determined by Nesslerization, P by the ammoniura-phospho-molybdat e method with 1,2,4-amino napthol sulphonic acid as the reducing agent visual estimation using root staining and microscopy Giovanetti and Mosse, 1979 (Masiunas, 1981). However, best shoot growth of perennial ryegrass occurs below 25 C (Sullivan and Sprague, 1949;Beevers and 47 Cooper, 1978). Root growth of perennial ryegrass is best below 26.6 to 32.3 C (Sullivan and Sprague, 1949).…”
mentioning
confidence: 99%
“…However, best shoot growth of perennial ryegrass occurs below 25 C (Sullivan and Sprague, 1949;Beevers and 47 Cooper, 1978). Root growth of perennial ryegrass is best below 26.6 to 32.3 C (Sullivan and Sprague, 1949).…”
mentioning
confidence: 99%